Microdiscectomy and Micro-Interlaminotomy Approach versus Standard Open Discectomy and Laminectomy: Comparison of Two Techniques. (May 2014) - Vanni, D.; Sirabella, F. S.; Pantalone, A.; Galzio, R.; Salini, V.; Magliani, V.
Introduction: Life expectancy increased, in the last years, have led to a larger proportion of elderly population and consequently to a greater incidence of degenerative arthritic disease. Lumbar spine is one of the most common localization. Therefore, low-back pain syndrome-increased prevalence was noted. In 20% of cases, patients have a degenerative disc disease associated with disc-root conflict and lumbar stenosis. Materials and Methods: An observational study was conducted, comparing microdiscectomy and micro-interlaminotomy approaches versus standard open discectomy and laminectomy. Since February 2010, 60 patients with lumbar disc herniation and unilateral root involvement with spinal canal stenosis were enrolled and divided into the two groups, homogeneous for age, sex, and disease severity (clinically and instrumentally assessed). Before surgical operation, all patients had been under medical therapy for at least 6 months without any clinical benefit. Of the 60 patients, 30 patients (group A) underwent microdiscectomy and micro-interlaminotomy and 30 patients (group B, control) underwent standard open approach. A clinical follow-up was performed at 1, 3, 6, and 12 months by mean of visual analog scale, neurogenic claudication outcome score, and oswestry low back pain disability questionnaire. A radiographic control was obtained at 1 and 12 months. Results: As time goes by, disc degeneration is associated with intervertebral space reduction, yellow ligament hypertrophy, and calcification. Intervertebral articulations overload and subsequent hypertrophy can lead to arthritis, epidural osteophytes, and spinal stenosis over time; then, disc-root conflict and lumbar stenosis may occur. Open discectomy and laminectomy has been the standard treatment over the last years. This approach allows a wide decompression, leading to good short-term results. This approach is invasive and not anatomic, as it is associated with a significant posterior elements demolition (both bony and ligamentous); then, instability may occur. This surgical technique is also associated with an increased intraoperative bleeding, leading to a dural adhesions great risk, fibrous scar, and recurrences. Conclusion: Microdiscectomy and micro-interlaminotomy approaches allow obtaining disc-roots conflict resolution and an effective medullary "recalibrage" in a noninvasive fashion. The minimal and controlled laminae demolition and the paraspinal muscles respect, result in a postoperative pain reduction, in a faster recovery time, in reduction of recurrence's risk, and in best long-term results. Disclosure of Interest None declared References Tharin S, Mayer E, Krishnaney A. Lumbar microdiscectomy and lumbar decompression improve functional outcomes and depression scores. Evid Based Spine Care J 2012;3(4):65–66 Schroeder JE, Dettori JR, Brodt ED, Kaplan L. Disc degeneration after disc herniation: are we accelerating the process? Evid Based Spine Care J 2012;3(4):33–40 Banczerowski P, Bognár L, Rappaport ZH, Veres R, Vajda J. Novel surgical approach in the management of longitudinal pathologies within the spinal canal: the split laminotomy and "archbone" technique: alternative to multilevel laminectomy or laminotomy. Adv Tech Stand Neurosurg 2014;41:47–70 Choi WS, Oh CH, Ji GY, et al. Spinal canal morphology and clinical outcomes of microsurgical bilateral decompression via a unilateral approach for lumbar spinal canal stenosis. Eur Spine J 2013